Participation of Planters in the Implementation of Community Palm Oil Rejuvenation (PSR) in Makmur Village, Pangkalan Kerinci District, Pelalawan Regency - Siahaan, Daniel Aliansyah; Hutabarat, Sakti; Novian, Novian (CV. Rayyan Dwi Bharata, 2024)
The research was carried out in the village of Makmur, Kerinci base district of Pelalawan. This research aims to analyze any factors that are significantly related to the participation of farmers in the implementation of the People's Sawit Rejuvenation (PSR) program in the village of Makmur, Kerinci Base district of Pelalawan. The sampling method used in this study is using simple random samplings. The data analysis used in this study is the Spearman Rank correlation test to measure the degree or intensity of the relationship between two variables, the free variable and the bound variable. The results of the research showed that there was a significant relationship between the factors of land size, income, motivation, experience, capital assistance and availability of means of production with the participation of farmers in the implementation of the People's Sawit Rejuvenation (PSR) program in the village of Makmur, Kerinci district. There is a need for increased participation of farmers through agricultural development to improve the capacity in palm coconut rejuvenation activities in the village of Makmur at the Kerinci Base district of Pelalawan, so that it can improve the value of palm farmers' use and it is necessary to monitor and evaluate the accompanying forces continuously so that there are no deviations in the program, so the People's Sawit Rejuvenate (PSR) program can continue for other farmers.